2010
DOI: 10.1007/s00223-010-9412-x
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of IL-6 by Osteoblasts Is Increased in Healthy Elderly Individuals: Stimulated Proliferation and Differentiation Are Unaffected by Age

Abstract: Increasing age is associated with reduced bone mineral content and increased risk of fractures. This is caused by a relative insufficiency of osteoblasts compared with osteoclasts. We therefore wanted to examine the potential differences in proliferation, differentiation, and expression of cytokines between human osteoblasts (hOBs) obtained from young and elderly individuals. Cultures of hOBs were obtained from 11 elderly (73-85 years) and 15 young (21-27 years) healthy individuals. The cells were stimulated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
10
0
3
Order By: Relevance
“…Igualmente, datos aportados por investigaciones posteriores al 2005 han demostrado que los incrementos en la síntesis y en la secreción de citocinas (IL-1 y IL-6) en sujetos ancianos tienen efectos negativos a nivel osteoarticular, debido a la pérdida de osteoblastos, además de que contribuye al deterioro en patologías inflamatorias relacionadas con la edad, como la osteoporosis y la osteoartritis. Los pacientes con polimialgia reumática, artritis reumatoide y dolor lumbar crónico causado por hernias discales, presentan mayores niveles de citocinas (TNF-α y IL-6, pero no de IL-1, ni sTNF-R), situación que mejora con un manejo farmacológico basado en glucocorticoides (Campos Kraychete D., 2010;Cutolo et al, 2006;Eriksen et al, 2010;Gomes et al, 2012;Marti et al, 2007).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Igualmente, datos aportados por investigaciones posteriores al 2005 han demostrado que los incrementos en la síntesis y en la secreción de citocinas (IL-1 y IL-6) en sujetos ancianos tienen efectos negativos a nivel osteoarticular, debido a la pérdida de osteoblastos, además de que contribuye al deterioro en patologías inflamatorias relacionadas con la edad, como la osteoporosis y la osteoartritis. Los pacientes con polimialgia reumática, artritis reumatoide y dolor lumbar crónico causado por hernias discales, presentan mayores niveles de citocinas (TNF-α y IL-6, pero no de IL-1, ni sTNF-R), situación que mejora con un manejo farmacológico basado en glucocorticoides (Campos Kraychete D., 2010;Cutolo et al, 2006;Eriksen et al, 2010;Gomes et al, 2012;Marti et al, 2007).…”
Section: Discussionunclassified
“…Concentraciones de citocinas son efectivas para el diagnóstico de las infecciones urinarias como predictor positivo, ya que estas se aumentan al tener la patología con su respectiva sintomatología clínica.Los pacientes con dolor lumbar crónico debido a hernias de disco presentan mayores niveles de TNF-alfa y de IL-6, pero no de IL-1 ni de sTNF-R.En pacientes con Epoc se encontraron niveles elevados de IL1-β y de PCR, asociados al grado de complejidad de la enfermedad: cuanto más graves los casos, mayores son los niveles de TNF-α y PCR. En pacientes fumadores los niveles basales de TNF-α están elevados (Eriksen et al, 2010). Con la edad los huesos van perdiendo la capacidad de estimulación, proliferación y diferenciación de osteoblastos, lo cual explica la aparición de la osteoporosis, íntimamente relacionada con el aumento de la IL-6 que conlleva al deterioro crónico del hueso.De acuerdo con los registros de este marcador se concluye la asociación de IL-6 con los criterios de hiperintensidad periventricular y de sustancia blanca, permitiendo un parámetro positivo al estar dicha cito-En la mayoría de casos reportados por pacientes de edad avanzada, la atrofia muscular se debe al sedentarismo.…”
unclassified
“…IL-6 has a range of pro-inflammatory and anti-inflammatory effects, and its levels correlate with the acute phase reactant C reactive protein 46. IL-6 also influences lipid and bone metabolism 47. Any inhibition of IL-6 production could therefore have multiple downstream effects on several organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies revealed that osteoblasts derived from aged donors present an altered phenotype and express lower levels of osteoblastic markers, such as type I collagen and decorin [30][31][32], even though other studies showed conflicting results [73]. Osteoblasts from elderly subjects express higher levels of IL-6, which is a pro-osteoclastogenic interleukin, and lower levels of OPG [64]. Conversely, in human cancellous bone obtained from young individuals, the expression of various osteoblastic bone-forming-related genes, including RUNX-2, Osterix, osteopontin and osteocalcin, as well as the expression of bone resorption markers, such as RANK-L and the matrix metalloproteinase 9 (MMP-9), were significantly higher compared to that of bone obtained from older subjects, indicating a decreased bone remodeling in elderly individuals associated with reduced bone density [74].…”
Section: Osteoblastsmentioning
confidence: 99%